Future Direction of AI in Block-chain for security systems – A Comprehensive Report - Wang, Haoxiang (Journal of Soft Computing Paradigm, 2022)
Currently, blockchain is a game-changing technology that’s revolutionizing the way applications are built because it eliminates the requirement for trust between network peers. Global and immutable repositories created by blockchain technology provide non-repudiation and accountability of the stored data. Because of this, processing and maintaining enormous volumes of data with ever-decreasing latencies are becoming more difficult. Therefore, artificial intelligence and machine learning approaches have made substantial advancements, paving the way for next-generation network infrastructure. The decentralization and tamper-proof nature of blockchain technology make it ideal for data exchange and privacy protection. This study paradigm may improve computer network reliability while also allowing new distributed and knowledge-driven security services and applications. Numerous issues are addressed in this work, including new cryptographic models for healthcare applications, intelligent threat-detection systems and novel approaches to consensus building in blockchains.